En rekonstruksjon av isutbredelsen i Rondane gjennom Weichsel med hovedvekt på glasialgeologi og isavsmeltingsformer - Kvisvik, Bjørn Christian (The University of Bergen, 2003)
The Rondane area has since the 18th century been of interest for scientists because of its glaciofluvial deposits (Gjessing, 1960), large number of periglacial phenomena (Barchs & Treter, 1976; Shakesby et al., 1987), and because the area is suggested to have been covered by the inland ice sheet until the early Holocene (Sollid & Sørbel, 1981). Sollid & Sørbel, (1981; 1994) have suggested that Rondane was covered by ice during the Younger Dryas (12800-11500 BP) chronozone, while Dahl et al., (1997) argues that the inland ice sheet was below 1240 meter above sea level (m asl.) during the same phase. Based on the mapping of superficial deposits and landforms a chronology of ice-cover and evolution of periglacial phenomena is presented. Three samples of glaciolacustrine sediments have been dated using the Optical Stimulated Luminescence (OSL) dating method. Erosional lateral drainage channels and accumulated glaciofluvial material are common and suggest a vertical downwasting ice mass. The general drainage has been towards the north, but a few crossing lateral drainage channels moves towards south and are the oldest. Traces of melt water 1800 m asl. on Høgronden reflect an vertically extensive ice cover during the Early Weichselian. Below 1200 m asl. in the central Rondane, accumulation of glaciolacustrine material covered by moraine and sandur sediments indicate one or two glacier advances during the Middle- and Late Weichselian. Glaciolacustrine sediments at 1070 and 1060 m asl. have been dated to 70 and 66 ka BP, belonging to a downwastage phase at the end of the Early Weichselian. There has been no temperate ice cover in the area since the Early Weichselian, indicating a limited extent of the ice cover in the Late- and Middle Weichselian. Two sets of marginal moraines after cirque glaciers at Høgronden indicates periods of cirque glaciation after the inland ice sheet disappeared from the area. Only one “definite” Holocene glacier advance was found, located close to Dørålvatnet at 1400 m asl. It was ...